2021
DOI: 10.37868/sei.v3i1.id138
|View full text |Cite
|
Sign up to set email alerts
|

Electricity generation potential of municipal solid wastes produced in the province of Edirne

Abstract: As a result of Turkey's economic growth, industrial development has accelerated across the country and this has ultimately led to the environmental sector and waste management gaining importance. In Turkey, where there is a depletion of natural resources, the expansion of energy demand, and the orientation in environmental technologies, waste is no longer a problematic issue that needs to be eliminated; but it has become a source of raw materials whose processing and recycling can be achieved with today's tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The gypseous content (X %) of the soil sample was found 37.3 %. As a result, the soil is categorized as Highly gypseous soil by Barazanji [6][7][8][9][10] (based on gypsum concentration), as shown in Table 2. According to (BS1377:1990) [7].…”
Section: Gypseous Soil Collapsibilitymentioning
confidence: 99%
“…The gypseous content (X %) of the soil sample was found 37.3 %. As a result, the soil is categorized as Highly gypseous soil by Barazanji [6][7][8][9][10] (based on gypsum concentration), as shown in Table 2. According to (BS1377:1990) [7].…”
Section: Gypseous Soil Collapsibilitymentioning
confidence: 99%
“…As it is known, solid waste generation rises in parallel with increasing population, living standards and technological developments, especially in cities [2]. Similarly, an increase is observed in the amount and type of solid waste generated in Tekirdağ [3,4]. The inadequacy of solid waste management in the province has led the local government to seek for new solutions [5].…”
Section: Introductionmentioning
confidence: 99%
“…2008 in Hanoi city on Vietnam. It was found that the concentration of PM10 is inversely proportional to the wind speed & mixing height inside the box [18][19][20]. The study aims to use the fixed box model to calculate the spread of pollutants (CO2, SO2, NOX, particulate) resulting from the burning of fuel used to produce electrical energy in the Nasiriyah city and to know the way they spread in the city through being affected by the wind speed and compare the results calculated from the model with the results measured by the lancom4 device.…”
Section: Introductionmentioning
confidence: 99%